HLA-DQB1* alleles and genetic susceptibility to type 1 diabetes mellitus - Mosaad, Youssef M (Baishideng Publishing Group Co., Limited, 2012)
AIM: To determine human leukocyte antigen (HLA)-DQB1 allele association with susceptibility to type 1 diabetes (T1D) and to clinical and laboratory findings. METHODS: This study was conducted on 85 unrelated Egyptian children with T1D recruited consecutively from the Pediatric Diabetes Endocrinology outpatients Clinic; Mansoura University Children’s Hospital, Egypt. Patient mean follow up period was 2.5 years. Patients were subdivided according to level of HbA1c (optimal/suboptimal control < 8.5% and poor control ≥ 8.5%). The control group consisted of 113 unrelated age- and sex-matched healthy subjects without T1D or other autoimmune diseases. Genomic DNA extraction was done for all subjects using a DNA isolation kit. HLA-Class II-DQB1 allele typing was carried out with a polymerase chain reaction-sequence-specific oligonucleotide probe using a INNO-LiPA HLA-DQB1 update kit. RESULTS: Significant differences were detected between Egyptian patients with T1D and control groups in the frequencies of DQB1*02 [44.4% vs 18.6%, corrected P value (Pc) < 0.001] and DQB1*03 (41.2% vs 24.4%, Pc < 0.001). Significant differences were also observed between control groups and T1D patients in the frequencies of DQB1*05 (14.6% vs 7.2%, P = 0.029) and DQB1*06 (34.1% vs 7.2%, P < 0.001). However, after correction for multiple comparisons, the significance was retained for HLA-DQB1*06 (Pc < 0.001) but lost for HLA-DQB1*05. HLA-DQB1*0201, *0202, *030201 were positively associated with T1D (Pc = 0.014, Pc < 0.001, and Pc < 0.001 respectively), while HLA-DQB1*060101 was negatively associated (Pc < 0.001) with the condition. Although the HLA-DQB1 alleles 030101 and 050101 were significantly higher in controls (P = 0.016, P = 0.025 respectively), both of them lost statistical significance after correction of P value. The frequency of the HLA-DQB1 genotypes 02/02, 02/03, and 03/03 was higher in T1D patients, and the frequency of the genotypes 03/06, 05/06, and 06/06 was higher in controls, these differences being statistically significant before correction. After correction, the genotypes 02/02, 02/03 in T1D, and the genotypes 03/06, 06/06 in controls were still significant (Pc = 0.01, Pc < 0.001, Pc < 0.001, and Pc = 0.04, respectively). Non-significant associations were found between the frequency HLA-DQB1 alleles and genotypes in T1D in relation to the grade of diabetic control, Microalbuminuria, age, gender, age of presentation, weight, height, frequency of diabetic ketoacidosis (P = 0.42), serum cholesterol, and fasting and post-prandial level of C-peptide (P = 0.83, P = 0.9, respectively). CONCLUSION: The Current work suggests that HLA-DQB1 alleles *030201, *0202, *0201, and genotypes 02/03, 02/02 may be susceptibility risk factors for development of T1D in Egyptian children, while the HLA-DQB1*060101 allele, and 03/06, 06/06 genotypes may be protective factors. HLA-DQB1 alleles and genotypes do not contribute to microalbuminuria or grade of diabetic control.